Optimization of Temperature and pH of Microbial Lipase in Coconut Pulp Media using Response Surface Methodology - I Dewa Gde Mayun Permana; Lutfi Suhendra (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2021)
The aim of this study is to determine the optimum temperature and pH of microbial lipases grown on coconut pulp media. The method used to obtain the optimum temperature and pH of lipase is Response Surface Methodology (RSM) with a central composite design (CCD). The result from the D-optimally analysis of RSM shows that the lipase temperature was 39.79oC and pH 5.13 with a theoretical maximum activity of 3.47 U/ml. The lipase activity of the validation results at temperature of 39.79oC and pH 5.13 was obtained as large as 3.41 U/ml or equal to 98.27% from the D-optimaly activity. Specific activity was obtained at 1,459 U/mg protein.